Treatment of Plantar Fasciitis in Patients with Calcaneal Spurs: Radiofrequency Thermal Ablation or Extracorporeal Shock Wave Therapy? - Tas, Nevsun Pihtili; Kaya, Oguz (Mdpi, 2023)
Background and Objectives: We aimed to compare the effectiveness of ESWT (Extracorporeal Shock Wave Therapy) and RFA (Radiofrequency Thermal Ablation) on pain, disability, and activity limitation in the treatment of plantar fasciitis in patients with calcaneal spurs. Materials and Methods: Patients who apply to Orthopedics and Traumatology and Physical Medicine and Rehabilitation departments with a complaint of heel pain are included in this retrospective study. We included patients diagnosed with calcaneal spurs who received treatment with ESWT (n = 80) and RFA (n = 79) between 1 August 2021 and 1 September 2022. All patients were evaluated using the Visual Analog Scale (VAS), Foot Function Index (FFI), and the Roles and Maudsley score (RM) before and after treatment. An evaluation was performed on average 6 months after treatment. Results: This study included 79 RFA patients (34 females and 45 males) with a mean age of 55.8 +/- 9.6 years and 80 ESWT patients (20 females and 60 males) with a mean age of 49.1 +/- 9.5 years. There was a significant decrease in VAS scores after treatment in both the RFA and ESWT groups (z: -4.98, z: -5.18, respectively, p < 0.001). The reductions in FFI pain, FFI activity restriction, FFI disability, and RM scores were significant in both groups, although the scores after treatment were lower in the RFA group. Conclusions: This study demonstrates that ESWT and RFA significantly reduced pain, disability, and activity restriction in the treatment of plantar fasciitis in patients with calcaneal spurs. ESWT proved particularly effective in alleviating pain, whereas RFA had more pronounced effects on reducing disability and activity limitations. The choice of treatment should be based on the patient's specific complaints.
Keywords: heel spur; extracorporeal shockwave therapy; radiofrequency ablation; visual analog scale; foot function index; the Roles and Maudsley score